Faktor Yang Mempengaruhi Hasil Belajar Kognitif Siswa Dalam Pembelajaran Jarak Jauh Berbasis E-Learning: FACTORS AFFECTING STUDENTS’ COGNITIVE LEARNING OUTCOMES ON DISTANCE LEARNING BASED ON E-LEARNING - Winanda, Verlia; Yana, Enceng (Perspektif Pendidikan dan Keguruan, 2021)
Cognitive ability is the intellectual ability of students in thinking, knowing and solving problems, and the level of success of students is the result of cognitive learning. The learning outcomes can be carried out in class or remotely if conditions do not allow. This study aims to analyze the factors that influence students' cognitive learning outcomes in distance learning based on e-learning. The research method used in this study is a literature study method using a qualitative approach. The results of this study indicate that the factors that influence students' cognitive learning outcomes in distance learning based on e-learning are (1) learning motivation factors, (2) learning readiness factors, (3) family environmental factors, and (4) media factors. distance learning support.